Incidence trends and gender differences in malignant mesothelioma in New South Wales, Australia - Hyland, Rebecca A; Ware, Sandra; Johnson, Anthony R; Yates, Deborah H (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'Features of malignant mesothelioma reportedly differ between men and women, including occupational asbestos exposure, histological subtype, and median survival. In this study, incidence trends and clinical features for malignant mesothelioma were compared between genders in New South Wales (NSW), where notification of malignant mesothelioma to the Central Cancer Registry is a statutory requirement. ' ' METHODS ': 'Notifications to the Central Cancer Registry were compared with those to the registry of the NSW Workers’ Compensation (Dust Diseases) Board. The latter includes occupational and clinical data. ' ' RESULTS ': 'Of the 3090 cases of malignant mesothelioma reported to the Central Cancer Registry between 1972 and 2004, 456 (15%) were female. Altogether 1995 malignant mesotheliomas were compensated between 1969 and 2004, of which 105 (5%) occurred among women. The incidence increased for both genders by approximately 15-fold. Median survival was similar for the men and women for all of the cases (7 versus 6 months), but was better among the women who received compensation (8.5 versus 10.4 months, P<0.0001). The mean disease latency (42.8 years) increased over the study period (P<0.001). ' ' CONCLUSIONS ': 'In New South Wales over the last 30 years, the total number of malignant mesotheliomas and the number of compensated cases of malignant mesothelioma have risen for both genders. The mean latency is increasing, and increasing numbers of “nonoccupational” cases are being reported. Survival remains poor.
Keywords: asbestos; Australia; gender difference; incidence trend; lung malignancy; malignant mesothelioma; woman